THE MOTIF OF DEVILISH MUSICIANS AND DANCERS IN FOLKLORISTIC AND ETHNOGRAPHIC WRITING MATERIALS - Piotrowski, Robert Piotr (Literatura Ludowa. Journal of Folklore and Popular Culture, 2018)
The starting point for the analysis proposed in this article is motifs of extraordinary/magical instruments, musicians and dance in folkloristic and ethnographic narratives. Looking at them, I am trying to pinpoint the perceptions of the demonic world present in the folk culture of the nineteenth century and the beginning of the twentieth century.